The contributions of gender identification and gender ideologies to the purposes of social media use in adolescence - Manago, Adriana M.; Walsh, Abigail S.; Barsigian, Logan L. (Frontiers in Psychology, 2023)
Gender differences in adolescent social media use are often documented in the research literature, yet few studies delve into why they occur. Accordingly, we investigated whether gender identification and gender ideologies are associated with five major purposes of social media use in adolescence (emotion and activity bonding with friends, social compensation, appearance validation, and bullying). Participants were 309 cisgender U.S. high school students (Mage = 15.74; 59% girls; 53% white) primarily using Instagram and Snapchat but also TikTok (more popular with girls) and Discord (more popular with boys) in 2019. Girls reported greater use of social media for emotion bonding, appearance validation, and social compensation compared to boys, who reported greater competitive activity bonding. Girls and boys did not differ in their use of social media for bullying. In linear regressions, masculinity ideology predicted purposes associated with girls (appearance validation, social compensation), as well as those associated with boys (competitive activity bonding), regardless of gender. Femininity ideology uniquely predicted emotion bonding and social compensation but only mediated the effect of gender for the latter. Findings illustrate that gender is important for understanding uses and gratifications of social media in adolescence, but traditional masculinity ideology is similar across genders and relates to multiple functions of social media in boys’ and girls’ lives. More work is needed to conceptualize gender beliefs and values in Gen Z, given recent challenges to gender binary ideology and low reliability of the scales in this study, which were developed before social media.